Optimizing Management of the Measurement System of the Technological Process - Jencurakova, Dana; Palencar, Rudolf (Manufacturing Technology Journal, 2016)
The present contribution represents the analysis and optimizing management of the measurement system of the technological process of pressing. It has been chosen the combination of appropriate methods for achieving the objective to minimize the cost of quality assurance of the measurement process by means its management. The quality of the measurement process has been verified by the reference standard (etalon). The optimization of evaluation measurement has been searched by utilizing QFD method (Quality Function Deployment). The subsequent optimization has been implemented by the taking into account the results of the use of the control charts and the deployment of QFD method and Kalman filter.
Keywords: Measurement System; Control Chart; QFD Method; Kalman Filter; Management; Quality; Optimization